Comentário do Artigo - Relationship between CA 15-3 serum levels and disease extent in predicting overall survival of breast cancer patients with newly diagnosed metastatic disease - André Cavalcanti Gentil (Instituto Nacional de Câncer José Alencar Gomes da Silva (INCA), 2001)
Comentário do artigo, Relationship between CA 15-3 serum levels and disease extent in predicting overall survival of breast cancer patients with newly diagnosed metastatic disease, publicado no Br J Cancer; 75(5): 698-702, 1997. doi: https://doi.org/10.1038/bjc.1997.124